Drying of thin porous disks from pore network simulations. Issue 6 (26th April 2018) - Vorhauer, N.; Tsotsas, E.; Prat, M.
ABSTRACT: Thin porous media (TPM) are porous layers that are characterized by a small thickness, usually orders of magnitude smaller than the lateral dimensions. We present pore network simulation revealing that drying of TPM is substantially different from drying of thicker porous media because of the impact of the small thickness of only a few pore layers on the liquid phase structure during drying. The small thickness limits the long-distance connectivity within the liquid clusters and thus causes the formation of smaller clusters characterized by shorter residence times. As a result of this stronger and earlier liquid phase fragmentation the drying of TPM is shown to be significantly more sensitive to the distribution of the evaporation flux at the surface. It is also shown that the drying behavior transition from thin to thick porous media is progressive. Moreover, it is discussed how an imposed temperature distribution can be used to control the evolution of the liquid cluster distribution in a TPM and thereby the evolution of the evaporation rate.